Advanced X-ray photoelectron spectroscopy of N-based ionic liquids - Santos, Ana (2018)
X-ray photoelectron spectroscopy (XPS) has been used to probe the influence of cation structure on fundamental interactions within Ionic Liquid (IL) systems. A series of guanidinium-based ILs have been investigated and cation-anion interactions have been studied to determine the effect of a highly charge delocalised cationic core on the electronic environment of the anion. These and sulfur-based cations were developed, and 13C-NMR comparisons addressed, along with the influence of sulfur functionalisation upon the electronic environments of the cationic component. These materials were then used to probe the composition and structural orientation of ions of the IL surface with resource to angle-resolved XPS (ARXPS) and particularly, energy-resolved XPS (ERXPS). Appropriate methodologies for both techniques were developed and fully verified, and the position of the anion ([NTf2]-) relative to cation (imidazolium, guanidinium and thioimidazolium) was found to support previous findings in the literature using other spectroscopic techniques. Additionally, ERXPS allowed for relative depth profiles not only of the anionic component, but also of the sulfur in the cationic component for the thioimidazolium bis(trifluoromethanesulfonyl)imide IL series.